Demographic and Clinical Findings of Cerebral Palsy Patients in Istanbul: A Multicenter Study - TÜRKDOĞAN, DİLŞAD (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2014)
Objective: The objective of this study is to identify epidemiological characteristics of patients with cerebral palsy (CP) in Istanbul, including demographic information, clinical types, risk factors, and some clinical features. Material and Methods: This is a retrospective and multicenter study, with the participation of 11 training and university hospitals in Istanbul. Demographic and clinical data of patients with CP presenting to university and training hospitals in Istanbul between 2005 and 2007 were recorded. Data were collected by the Istanbul Cerebral Palsy Study Group (ICPSG). Results: A total of 730 patients with a mean age of 7.27 +/- 4.63 (2-18 years) were enrolled into the study; 429 (58.8%) of the patients were male and 301 (41.2%) were female. During clinical typing, it was seen that 91% of the patients were spastic, 3.6% was mixed, 3.2% was dyskinetic, and 0.7% was ataxic. Also, 51.9 % of the patients had a diagnosis of CP during 0-6 months of age, 24.6% had the diagnosis during 6-12 months of age, and 23.5% in the twelfth month or later. Of the cases, 32% had speech disorders, 23.1% had mental retardation, and 20.9% had epilepsy. Conclusion: There are few studies about the demographic characteristics of patients with SP in our country. This study is a pilot study to determine the profile of cases of CP patients in our country and to create a CP patient pool for the future prospective studies.
Keywords: Cerebral palsy; demographic features; epidemiology; spasticity; epilepsy; RISK-FACTORS; CONSANGUINEOUS MARRIAGE; CHANGING PANORAMA; TURKISH CHILDREN; PREVALENCE; SWEDEN; DISORDERS; TURKEY; ORIGIN